Representasi Perundungan dalam Novel Manusia-Manusia Teluk karya Artie Ahmad: Representation of Offenses in Novel Manusia-Manusia Teluk by Artie Ahmad - Berliana, Bella; Trianton, Teguh (Kibas Cenderawasih, 2022)
The purpose of this study is to describe the types of bullying in the novel Manusia-Manusia Teluk by Artie Ahmad. This research belongs to the type of qualitative research with qualitative content analysis methods. The approach used is literary psychology. The source of the data for this research is a novel Manusia-Manusia Teluk by Artie Ahmad. The research data are in the form of words and sentences that represent the types of bullying in the novel Human-Man Teluk by Artie Ahmad. The data were collected using document or library study techniques. Meanwhile, data analysis was carried out through three stages consisting of: data reduction, data presentation, and drawing conclusions. The results showed that the novel Man-Man Teluk by Artie Ahmad represented four types of bullying, namely: (1) physical bullying; (2) sexual harassment; (3) verbal bullying; and (4) mental bullying.